INDUSTRIAL RELATIONSHIP DISPUTE RESOLUTION THAT MEETS THE PRINCIPLE OF FAST, LOW COST AND EFFICIENT - Haryanto Haryanto; Arie Purnomosidi (Surakarta Law and Society Journal, 2022)
The purpose of this study is to determine whether the settlement of industrial relations has met the principles of fast, low cost and efficient. The type of research used is normative legal research. By using a statutory approach and a conceptual approach. the data used is secondary data consisting of primary, secondary and tertiary legal materials. data analysis using deductive method. The Industrial Relations Court trial process which must be carried out by workers and companies at least 8 (eight) sessions is added to the waiting period in the Cassation and Review case process at the Supreme Court for which there is no time limit, then the waiting period for the Cassation and Review administration process Again, which also has no time limit, then the series of many trials and the length of the cassation process, judicial review to execution, of course, all of them simultaneously require a large amount of money, so it can be said that in theory there are no costs in handling cases, but in practice workers will spend a lot of money, thus the principle of low cost is not implemented. Keywords: dispute resolution, industrial relationship, the principle of fast, low cost and efficient.